Aprovechamiento de recursos pesqueros infrautilizados para la obtención de alimentos mejorados para el cultivo de peces - Aurrekoetxea, G.; Perera, M.N. (2002)
Several underutilised fishery resources were analysed, including low market value species and fish processing byproducts, and then one was selected due to its composition, amount and availability for high quality protein production for juvenile gilthead sea bream and turbot diets. Among the available extraction technologies, enzymatic hydrolysis was selected, since the resulting final product has high nutritional value. Four commercial enzymes were tested to determine their activity, and the one with the best activity/cost relationship was chosen. Finally, the conditions for hydrolysate production were optimised, and in vitrodigestibility of the protein obtained was compared with that of an untreated product. Se caracterizaron varios recursos pesqueros infrautilizados (especies de bajo interés, residuos de la industria transformadora.) seleccionando uno de ellos según su composición, volumen y disponibilidad para la obtención de proteína de alta calidad apta para dietas de alevines de dorada o rodaballo. Como tecnología de extracción se empleó la hidrólisis enzimática, cuyas condiciones de proceso permiten obtener un producto final de alto valor nutritivo. Se ensayaron cuatro enzimas comerciales determinando su actividad y se seleccionó aquélla de mejor relación actividad/coste. Finalmente, se optimizaron las condiciones de obtención del hidrolizado y se comparó la digestibilidad in vitro de la proteína obtenida con la de un producto no tratado. Instituto Español de Oceanografía